A Discrepancy Analysis of Authentic Assessment Implementation in EFL Classroom of Senior High School In Badung Based On Curriculum 2013 - Kardiana, I.G. (Jurnal Pendidikan Bahasa Inggris Indonesia, 2019)
This study aimed at investigating and describing the discrepancy of authentic assessment implementation in EFL classroom of SMAN 1 Abiansemal based on the 2013 Curriculum and the teacher’s belief on the authentic assessment implementation. This is an evaluative study, especially educational evaluation. The subjects of this research are three EFL teachers in SMAN 1 Abiansemal. The data were collected by using four methods of data collection, namely documenting, observation, in depth interview and questionnaire. Based on the methods of data collection, there were instruments utilized such as observation sheet, teacher’s belief questionnaires, and interview guide. The data obtained from the observation sheet and questionnaire of teacher belief were analyzed and calculated by using Ideal Theoretical Reference Criteria. From the data analysis it was found that (i) the discrepancy of authentic assessment implementation in EFL classroom of SMA Negeri 1 Abiansemal based on the curriculum 2013 is categorized into narrow, specifically, self assessment is categorized into narrow, portfolio assessment is categorized into moderate, performance assessment is categorized into very narrow. and project assessment is categorized into narrow and (ii) The teachers’ beliefs about authentic assessment implementation is categorized into very positive. This results means that the implementaion of authentic assessment in Curriculum 2013 can not be achieved ideally.